The Roles of Quantity Surveyor in Sustainable Development within Islamic Framework - Ahmad Nizam, Ahmad Aliff; Hasan, Sharina Farihah (Research in Management of Technology and Business, 2024)
Islam offers a broad ethical framework and concepts that can direct sustainable practices because it is a holistic way of life. Integrating the Islamic framework into sustainable development practices requires a deep understanding of both sustainable development principles and Islamic teachings. This includes knowledge of the Maqasid Shariah, which provides a comprehensive framework for Islamic values and objectives and the concept of khalifa, which sees human as the representative in managing the earth. The study discusses Islamic framework from the context of Maqasid Shariah and the concept of khalifa on earth. Existing literature on the roles of quantity surveyors in sustainable development primarily focuses on environmental and economic aspects, limited attention may be given to the integration of Islamic frameworks. Understanding the role of quantity surveyors in sustainable development within Islamic frameworks is paramount. This paper aims to examine the opportunities for quantity surveyors in implementing Islamic frameworks into their professional roles and responsibilities in sustainable development. Methodology for the study involves reviews of relevant literature and in-depth structured interviews with five (5) experts. The findings indicate that quantity surveyors have the opportunity to implement the Maqasid Shariah framework into their roles in sustainable development.